Pemanfaatan Bahan Alam sebagai Media Pembelajaran untuk Meningkatkan Kreativitas Anak Usia Dini melalui Kegiatan Kolase - Rustika, Lena; Alam, Syah Khalif (IKIP Siliwangi, 2025)
Early childhood creativity can be developed through education. Education is a right and necessity for early childhood; however, some children have not yet had the opportunity to develop their creative skills through collage techniques. This method can help children enrich their imagination and generate creative ideas when making collages. The purpose of this study was to analyze early childhood creativity using the collage method. The research method employed was Classroom Action Research (CAR), with observation used as data collection techniques. The subjects of this study were 17 children in Group B at KB Nur Wafa. Data were analyzed using both quantitative and qualitative descriptive methods. Based on the results, it can be concluded that collage activities using natural materials—such as leaves, flowers, and other organic items—provided children with opportunities to create various shapes and image variations, make their own art, and tell stories about their creations. The results also showed an increase in children's creativity: in the pre-cycle phase, 11.8% of children were categorized as “Developing as Expected” (BSH); in Cycle I, this increased to 23.5%, with 35.3% in the “Developing Very Well” category. In Cycle II, 58.8% of children were categorized as “Developing as Expected” and 23.5% as “Developing Very Well.”